2003
DOI: 10.1785/0120020228
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Mechanics of the Hayward-Rodgers Creek Fault Step-Over, San Francisco Bay, California

Abstract: A dilatational step-over between the right-lateral Hayward and Rodgers Creek faults lies beneath San Pablo Bay in the San Francisco Bay area. A key seismic hazard issue is whether an earthquake on one of the faults could rupture through the step-over, enhancing its maximum possible magnitude. If ruptures are terminated at the step-over, then another important issue is how strain transfers through the step. We developed a combined seismic reflection and refraction cross section across south San Pablo Bay and fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
32
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 42 publications
6
32
0
Order By: Relevance
“…The basin is defined by velocity anomaly and gravity anomaly lows to be 10 to 20 km long, 5 to 10 km wide, and at least 3 km thick (Figures 3a, 3b, 5b, and 8). The San Pablo Basin has been viewed as a narrow pull‐apart basin between the Hayward and Rodgers Creek Faults [ Smith , 1992; Wright and Smith , 1992], but recently it has been recognized to be a broader basin extending to the east of the Rodgers Creek Fault [ Parsons et al , 2003]. Our model images a strong velocity contrast across the western margin of the basin and a lesser, but still identifiable velocity contrast on its eastern margin.…”
Section: Model Resultsmentioning
confidence: 88%
“…The basin is defined by velocity anomaly and gravity anomaly lows to be 10 to 20 km long, 5 to 10 km wide, and at least 3 km thick (Figures 3a, 3b, 5b, and 8). The San Pablo Basin has been viewed as a narrow pull‐apart basin between the Hayward and Rodgers Creek Faults [ Smith , 1992; Wright and Smith , 1992], but recently it has been recognized to be a broader basin extending to the east of the Rodgers Creek Fault [ Parsons et al , 2003]. Our model images a strong velocity contrast across the western margin of the basin and a lesser, but still identifiable velocity contrast on its eastern margin.…”
Section: Model Resultsmentioning
confidence: 88%
“…In the second set of models, the initial fault geometries follow those inferred from two sets of geophysical observations, including earlier work (Parsons et al, ), and more recent imaging (Watt et al, ). Earlier geophysical data indicate that the Rodgers Creek Fault extends far into the San Pablo Bay (Parsons et al, ), forming an overlapping step over with the Hayward Fault. However, Watt et al () do not find evidence for activity along this fault in the upper 2–5 m and map an underlapping step over within the bay.…”
Section: Methodsmentioning
confidence: 93%
“…The red box indicates study area shown. (b) Fault geometry of step over from previous interpretations in black dashed lines (Parsons et al, ) and more recent interpretations in solid gray lines (Watt et al, ).…”
Section: Introductionmentioning
confidence: 88%
“…2) to emerge as the right-lateral Hayward fault in the eastern San Francisco Bay region west of Berkeley (Brown, 1970;Wright and Smith, 1992;Parsons et al, 2003). North of Santa Rosa, the Rodgers Creek fault zone consists of the northern Rodgers Creek fault zone, which locally is referred to as the Healdsburg fault segment of the Rodgers Creek fault zone.…”
Section: Fault Nomenclaturementioning
confidence: 99%